Penerapan Metode Monte Carlo untuk Simulasi Prediksi Tingkat Penjualan Coklat Khas Dubai - Desi, Efani; Aliyah, Siti; Dari, Wulan; Nasution, Fitri Pranita; Maisaroh, Enni (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
DarkChoco, which sells Dubai chocolate, has seen its sales increase every day, but this situation has affected the level of service to customers because the ingredients used to make the chocolate run out quickly. There are some customers who cannot taste and get the Dubai chocolate. This case will lead to fewer customers. So this research was conducted to predict sales in maintaining the availability of materials so that the services will increase again. The method that will be used in this research uses the Monte Carlo method by processing Dubai Viral Chocolate sales data in 2021, 2022 and 2023. This study aims to simulate the prediction of the sales level of Dubai specialty chocolate by applying the Monte Carlo method. Dubai specialty chocolate is a product with high market potential and significant demand fluctuations, so accurate sales prediction is very important for business decision making. The simulation of the sales forecast will show an average accuracy rate of about 94.5%, which means that the forecast is quite close to the actual data. Some months with large deviations (February, March, May, August, December) indicate potential seasonal variability or other factors that need attention. This simulation model is effective for sales forecasting and planning by taking uncertainty into account. Thus, this method is capable of producing forecasts that are more realistic and informative than conventional methods. The results show that the application of Monte Carlo method is able to provide a comprehensive overview of sales simulation and predict sales levels with sufficient accuracy, and this Monte Carlo method can also be an effective tool in helping companies manage inventory and marketing strategies for Dubai specialty chocolates to improve operational efficiency and business profits in the future.